Emotional and behavioral outcomes in childhood for survivors of invasive group B Streptococcus disease in infancy: Findings from 5 low- and middle-income countries - Chandna, J; Liu, W-H; Dangor, Z; Leahy, S; Sridhar, S; John, HB; Mucasse, H; Bassat, Q; Bardaji, A; Abubakar, A; Nasambu, C; Newton, CR; et al. (Oxford University Press, 2021)
Background Survivors of invasive group B Streptococcus (iGBS) disease, notably meningitis, are at increased risk of neurodevelopmental impairment. However, the limited studies to date have a median follow-up to 18 months and have mainly focused on moderate or severe neurodevelopmental impairment, with no previous studies on emotional-behavioral problems among iGBS survivors.